Pengaruh Body Image dan Penerimaan Diri terhadap Kesehatan Mental Remaja di Kec. Selebar Kota Bengkulu - Oktapia, Selpina; Anita, Fifi; Zalianti, Venia; Badriyah, Lailatul (Yayasan Darussalam Bengkulu, 2022)
This research aims to see the influence of body image and self-acceptance on the mental health of adolescents in sub-districts as wide as the city of Bengkulu. This research uses quantitative methods, the data collection technique is by distributing a questionnaire with 30 items distributed. The samples studied were teenagers in sub-districts as wide as the city of Bengkulu. Data collection was 101 respondents. This research was analyzed using quantitative analysis using spps 22 by testing regression, correlation, normality test, reliability test, and R square. Based on the results of this study, it shows that the influence of body image and self-acceptance on the mental health of adolescents in sub-districts as wide as the city of Bengkulu is in the weak category, namely 26.7%.